2012
DOI: 10.3390/s120607682
|View full text |Cite
|
Sign up to set email alerts
|

An Accurately Controlled Antagonistic Shape Memory Alloy Actuator with Self-Sensing

Abstract: With the progress of miniaturization, shape memory alloy (SMA) actuators exhibit high energy density, self-sensing ability and ease of fabrication, which make them well suited for practical applications. This paper presents a self-sensing controlled actuator drive that was designed using antagonistic pairs of SMA wires. Under a certain pre-strain and duty cycle, the stress between two wires becomes constant. Meanwhile, the strain to resistance curve can minimize the hysteresis gap between the heating and the c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
1

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 63 publications
(43 citation statements)
references
References 20 publications
0
39
0
1
Order By: Relevance
“…As noted by Lan and Fan 9 as well as in our previous work, 24 under convenient pre-strain, the heating and cooling paths are already quite close, and a polynomial model with one-to-one mapping is sufficient to describe the paths. In this experiment, the MATLAB ''polyfit'' function was used to obtain the coefficients of the polynomials.…”
Section: S-r Curve Disturbed By Internal Forcementioning
confidence: 89%
See 3 more Smart Citations
“…As noted by Lan and Fan 9 as well as in our previous work, 24 under convenient pre-strain, the heating and cooling paths are already quite close, and a polynomial model with one-to-one mapping is sufficient to describe the paths. In this experiment, the MATLAB ''polyfit'' function was used to obtain the coefficients of the polynomials.…”
Section: S-r Curve Disturbed By Internal Forcementioning
confidence: 89%
“…Within the antagonistic pair of SMA wires actuator, enough pre-strain could also maintain enough inner stress between the wires, which minimized the hysteresis gap with the same principle. Based on our previous study 24 of the pair of SMA wires actuator, it is concluded that the hysteresis gap between the heating and cooling curves is directly influenced by real-time internal force. With correct pre-strain, the hysteresis gap might be minimized.…”
Section: S-r Curve Disturbed By Internal Forcementioning
confidence: 99%
See 2 more Smart Citations
“…Note that the resistance of the actuator might also undergo mild changes during phase transition, the change is less than 15% [29] and is considered to be constant in this work. Under a constant (quasi-static) voltage V , the steady-state temperature T can be computed as…”
Section: B Steady-state Voltage As Temperature Surrogatementioning
confidence: 99%